Peran Sistem Keuangan Desa dalam Mendukung Akuntabilitas Keuangan Pemerintah Desa di Desa Banda Kecamatan Tarano - Hermawati Hermawati; Denny Hambali (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to examine the role of the Village Financial System (Siskeudes) in supporting village government financial accountability in Banda Village, Tarano District. The study uses a qualitative descriptive approach, with data collected through interviews and documentation involving the Village Secretary and the Siskeudes Operator as key informants in village financial management. Financial accountability is a crucial element of village governance because it ensures transparency, responsibility, compliance, and public trust in the use of village funds. The findings show that Siskeudes strengthens financial accountability by improving the orderliness of recording, accelerating the preparation of accountability reports, reducing manual recording errors, and providing more structured financial information for supervision and public accountability. Compared with previous studies that generally emphasize Siskeudes as an administrative reporting application, this study highlights its added value as a digital accountability mechanism that connects transparency, financial responsibility, and regulatory compliance in a rural village context. The academic contribution of this study lies in extending the discussion of village financial governance by showing how information systems support stewardship practices and digital accountability at the village level, particularly in Banda Village, which still faces limited internet infrastructure and human resource constraints. The main challenge found in the implementation process is unstable internet connectivity, which can delay data entry and system operation. Therefore, strengthening rural digital infrastructure, improving operator capacity, and enhancing coordination among central, regional, and village governments are necessary to ensure the sustainable implementation of Siskeudes and the optimal achievement of village financial accountability.